Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1002/(sici)1096-9861(19990614)408:4<515::aid-cne6>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Glycine immunoreactivity of multipolar neurons in the ventral cochlear nucleus which project to the dorsal cochlear nucleus

Abstract: Certain distinct populations of neurons in the dorsal cochlear nucleus are inhibited by a neural source that is responsive to a wide range of acoustic frequencies. In this study, we examined the glycine immunoreactivity of two types of ventral cochlear nucleus neurons (planar and radiate) in the rat which project to the dorsal cochlear nucleus (DCN) and thus, might be responsible for this inhibition. Previously, we proposed that planar neurons provided a tonotopic and narrowly tuned input to the DCN, whereas r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 0 publications
3
49
1
Order By: Relevance
“…This observation suggests that the On-C and On-L axons may form axosomatic synaptic contacts of the kind commonly associated with inhibitory synaptic input. This suggestion is supported by both the imrnunohistochemical evidence for glycinergic transmission in VCN large stellate cells which innervate DCN (Doucet et al 1999;Alibardi 2001) and the presence of glycinergic terminals on the somata of fusiform cells in the DCN (Osen et al 1990). There is also extensive physiological evidence for strychninesensitive inhibitory input to type II cells in DCN (Davis and Young 2000).…”
Section: Local Axonal Projectionsmentioning
confidence: 91%
See 1 more Smart Citation
“…This observation suggests that the On-C and On-L axons may form axosomatic synaptic contacts of the kind commonly associated with inhibitory synaptic input. This suggestion is supported by both the imrnunohistochemical evidence for glycinergic transmission in VCN large stellate cells which innervate DCN (Doucet et al 1999;Alibardi 2001) and the presence of glycinergic terminals on the somata of fusiform cells in the DCN (Osen et al 1990). There is also extensive physiological evidence for strychninesensitive inhibitory input to type II cells in DCN (Davis and Young 2000).…”
Section: Local Axonal Projectionsmentioning
confidence: 91%
“…These onset cells integrate inputs from auditory nerve fibers with a broad range of BFs , acting as coincidence detectors with a relatively narrow coincidence window ; they respond better to broadband signals than to pure tones; and they exhibit relatively wide dynamic ranges (Smith and Rhode 1986;Winter and Palmer 1995). Physiologically characterized, VCN onset cells have been found to exhibit large multipolar morphology (Smith and Rhode 1989), and VCN cells with this morphology have been found to be glycinergic (Doucet et al 1999) and are thought to provide inhibition of other neurones in the cochlear nucleus such as the T stellate cells (Ferragamo et al 1998). …”
Section: Innervation Of the Ipsilateral Dcnmentioning
confidence: 99%
“…Tract-tracing studies have confirmed that these neurons project to the contralateral cochlear nucleus (Arnott et al 2004;Smith et al 2005;Doucet and Ryugo 2006). Because Type II (D-stellate) neurons are glycinergic (Wenthold 1987;Alibardi, 1998;Doucet et al 1999), they are thought to be a major source of the short-latency inhibition that is observed in the cochlear nucleus after contralateral stimulation (Pfalz 1962;Mast 1970;Young and Brownell 1976;Babalian et al 1999;Needham and Paolini 2003;Shore et al 2003). However, the majority of commissural neurons lack the anatomical features that are characteristic of the Type II morphology (Shore et al 1992;Schofield and Cant 1996b;Alibardi 1998;Doucet and Ryugo 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Multipolar cells have also been classified by number of terminals on the soma (Cant, 1981) and by shape of the soma (Doucet and Ryugo, 1997;Doucet et al, 1999). The preponderance of "planar" multipolar cells in PVCN (Doucet et al, 1999) suggests that this subgroup may correspond to the MOC reflex interneurons.Multipolar cells produce a chopper discharge Rouiller and Ryugo, 1984; reviewed by Rhode and Greenberg, 1992), and several physiological subgroups have been described. Chop-S or "regular" choppers and chop-T or "irregular" choppers are distinguished by interspike intervals (Young et al, 1988).…”
mentioning
confidence: 99%